Inhibition of fatty acid synthase sensitizes prostate cancer cells to radiotherapy - Rae, Colin; Haberkorn, Uwe; Babich, John W.; Mairs, Robert J. (Radiation research, 2015)
Many common human cancers, including colon, prostate and breast cancer, express high levels of fatty acid synthase compared to normal human tissues. This elevated expression is associated with protection against apoptosis, increased metastasis and poor prognosis. Inhibitors of fatty acid synthase, such as the cerulenin synthetic analog C75, decrease prostate cancer cell proliferation, increase apoptosis and decrease tumor growth in experimental models. Although radiotherapy is widely used in the treatment of prostate cancer patients, the risk of damage to neighboring normal organs limits the radiation dose that can be delivered. In this study, we examined the potential of fatty acid synthase inhibition to sensitize prostate cancer cells to radiotherapy. The efficacy of C75 alone or in combination with X irradiation was examined in monolayers and in multicellular tumor spheroids. Treatment with C75 alone decreased clonogenic survival, an effect that was abrogated by the antioxidant. C75 treatment also delayed spheroid growth in a concentration-dependent manner. The radiosensitizing effect of C75 was indicated by combination index values between 0.65 and 0.71 and the reduced surviving fraction of clonogens, in response to 2 Gy X irradiation, from 0.51 to 0.30 and 0.11 in the presence of 25 and 35 μM C75, respectively. This increased sensitivity to radiation was reduced by the presence of the antioxidant. The C75 treatment also enhanced the spheroid growth delay induced by X irradiation in a supra-additive manner. The level of radiation-induced apoptosis in prostate cancer cells was increased further by C75, which induced cell cycle arrest in the G2/M phase, but only at a concentration greater than that required for radiosensitization. Radiation-induced G2/M blockade was not affected by C75 treatment. These results suggest the potential use of fatty acid synthase inhibition to enhance the efficacy of radiotherapy of prostate carcinoma and that C75-dependent cell cycle arrest is not responsible for its radiosensitizing effect.
Gesehen am 17.07.2020